1993
DOI: 10.1007/bf02913735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical stimulation on the production of soluble bone factors in cultured fetal mouse calvariae

Abstract: Mechanical stimulation by intermittent compressive force (ICF) stimulates bone formation and inhibits bone resorption in cultured fetal mouse bone. Fetal bone tissue can produce autocrine factors that stimulate bone cell replication and matrix formation, and paracrine factors that increase the formation of osteoclast precursor-like cells from bone marrow. In the present study, we have tested whether ICF affects the production of such local factors in fetal mouse calvariae. Calvariae were cultured for 4 days in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Hasegawa et al (19) demonstrated a 64% increase in proliferation of calvarial cells exposed to hyperphysiological strains of 40,000 p with a continuous single cycle of deformation. The current study, as well as others (6,9,20,21,25,29,30), documented proliferative responses (over a wide variety of plating and mechanical conditions) in which 8-64% of the cells were labeled. Therefore, in vitro descriptions of cellular response to mechanical strain often results in proliferative responses at high strain magnitudes.…”
Section: Discussionmentioning
confidence: 90%
“…Hasegawa et al (19) demonstrated a 64% increase in proliferation of calvarial cells exposed to hyperphysiological strains of 40,000 p with a continuous single cycle of deformation. The current study, as well as others (6,9,20,21,25,29,30), documented proliferative responses (over a wide variety of plating and mechanical conditions) in which 8-64% of the cells were labeled. Therefore, in vitro descriptions of cellular response to mechanical strain often results in proliferative responses at high strain magnitudes.…”
Section: Discussionmentioning
confidence: 90%
“…Transmission of mechanical force from the bone matrix to the osteocyte cell membrane was initially thought to occur via direct sensing of whole-tissue strains on the osteocyte surface. However, strains applied to whole bone in vivo during normal locomotion are typically between 0.04–0.3% [ 2 , 3 ], an order of magnitude smaller than the strain necessary to elicit a biochemical response at the osteocyte plasma membrane (1–10%) [ 4 , 5 , 6 ]. Thus, a mechanism other than direct force transmission from the bone matrix must account for the ability of osteocytes to perceive mechanical input.…”
Section: Introductionmentioning
confidence: 99%
“…3,4), an order of magnitude smaller than the strain necessary to elicit a biochemical response at the osteocyte plasma membrane (1-10%) (ref. [5][6][7]. Thus, a mechanism other than direct force transmission from the bone matrix must account for the ability of osteocytes to perceive mechanical input.…”
Section: Introductionmentioning
confidence: 99%